New insights into the salt-responsive regulation in eelgrass at transcriptional and post-transcriptional levels - Zhao, Huan; Dong, Xu; Yang, Dazuo; Ge, Qingchao; Lu, Peng; Liu, Chang (Frontiers in Plant Science, 2025)
IntroductionThe adaptation mechanisms of marine plants to the environments have garnered significant attention in recent years. Eelgrass (Zostera marina), a representative marine angiosperm, serves as an ideal model for investigating the mechanisms underlying salt tolerance.MethodsThis study integrated mRNA, sRNA, and degradome sequencing data to identify key genes associated with salt tolerance in eelgrass.ResultsThe results indicate that a series of genes involved in biological processes such as “in response to water deprivation” and “biosynthesis of secondary metabolites” respond to salt stress. Analysis of cis-regulatory elements and expression similarities suggests that the ABA synthase 9-cis-epoxycarotenoid dioxygenase (NCED) may be regulated by ERF members, while phenylalanine ammonia-lyase (PAL) may be regulated by MYB members. At the post-transcriptional regulation level, miRNA156 and miRNA166 might be involved in the response by regulating potential target genes, such as members of the WRKY and HD-ZIP families. Additionally, eelgrass exhibits unique responses to salt, such as the up-regulation of genes involved in the “fucose biosynthetic process”. These findings enhance our understanding of how eelgrass adapts to the marine environment.DiscussionAs a marine monocotyledon, eelgrass is helpful to find conserved salt tolerance mechanisms by cross-species comparison. By examining the transcriptional responses of homologous genes in eelgrass, rice, and maize, we identified several groups of genes that are conserved in their response to salt stress. These conserved gene resources may provide targets for genetic engineering to improve the salt tolerance of crops.